The nomenclature of two names proposed for Portuguese taxa of Calendula (Asteraceae) by Lange in 1883 - Figueiredo, Estrela; Smith, Gideon F.; Silveira, Paulo (Phytotaxa, 2018)
Confusion has existed about the status and authorship of some of the new names published in an article entitled ‘Notas’ that appeared in 1883 in the first volume of the Portuguese journal Boletim da Sociedade Broteriana. The ‘Notas’ consisted of several notes (A to I); one of these, Note A, was unambiguously authored by Ficalho (Francisco Manuel de Melo Breyner; 1837–1903), as Conde de Ficalho, and ‘Lisbon’ appeared at the bottom of the note. It is not immediately clear who authored the other notes. However, these must be attributed to Henriques (Júlio Augusto Henriques; 1838–1928), the editor of the volume. Perhaps counter-intuitively, these ‘Notas’ complemented another paper, a list of plants distributed to members of the society (“Especies distribuidas”), which appeared on pages 27–47 of the same volume. For this reason the ‘Notas’ were often cryptic, and genera, for example, were referenced by their initial letters only. For instance, in Note E a new species was described in Latin, under the genus “P.”; a full name was not provided for the genus, and neither for the new species. However, in the article on species distributed (p. 42) Pulicaria microcephala Lange is listed under the genus Pulicaria and is cross-referenced back to Note E. Pulicaria microcephala is not listed in the International Plant Name Index (IPNI), but is recorded in the Euro+Med PlantBase by Greuter (2006+), where it is treated as an accepted name with the citation Lange in Bol. Soc. Brot. 1: 42, 50. 1883.